Comparison of outcomes following prepectoral and subpectoral implants for breast reconstruction in patients with breast cancer - Zhang, Jun; An, Ran; Yu, Zhi-Hao; Zhang, Li (Frontiers in Oncology, 2025)
BackgroundIn recent years, different approaches to implant-based breast reconstruction have increasingly become an important option to meet both the treatment and postoperative aesthetic needs of breast cancer patients. This study selected two commonly used techniques for the prepectoral approach: single-incision, gas-inflated endoscopic prepectoral breast reconstruction (SIE-BR) and open prepectoral implant-based breast reconstruction (C-BR), as well as a commonly used technique for the subpectoral approach: open subpectoral implant-based breast reconstruction (SI-BR). By comparing the clinical efficacy and aesthetic outcomes of these three techniques in the treatment of breast cancer patients, this study aims to summarize the advantages of the prepectoral approach.MethodsThis study screened the clinicopathological data of a total of 136 breast cancer patients from January 2023 to December 2023. Among them, 38 patients underwent SIE-BR, 51 patients underwent C-BR, and 47 patients underwent SI-BR. The patient characteristics, intraoperative and postoperative conditions were analyzed in detail, and satisfaction was assessed using the BREAST-Q questionnaire.ResultsThe SIE-BR group had the longest surgery time, followed by the SI-BR group, with the C-BR group having the shortest surgery time. The C-BR group had the least blood loss, while the SIE-BR group had the most. The C-BR group also had the lowest drainage volume, and the SIE-BR group had the highest. Patients were categorized into a prepectoral implant-based reconstruction group (PIBR) and a subpectoral implant-based reconstruction group (SIBR). None of the patients experienced implant loss or flap necrosis. The PIBR group had significantly lower rates of wound infection, capsular contracture, and chest muscle pain compared to the SIBR group. The rates of wound dehiscence and implant wrinkling were statistically similar between the two groups. BREAST-Q scores indicated similar satisfaction in terms of breast appearance and sexual life between the groups, but the PIBR group showed significantly better scores in physical health (chest muscle function preservation) and mental health. Additional advantages of the prepectoral approach, including less postoperative pain, reduced movement-related deformity, and shorter surgery time, have contributed to the steady growth of this technique in recent years.ConclusionThe three implant-based breast reconstruction techniques mentioned above are safe and feasible. Compared to the previously more common subpectoral approach, the prepectoral approach improves patients’ postoperative physical and psychological comfort, making it an ideal surgical option.